2020
DOI: 10.1371/journal.pone.0236967
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of visual attention: SSVEP frequency-tagging moving targets

Abstract: Previous research has shown that visual attention does not always exactly follow gaze direction, leading to the concepts of overt and covert attention. However, it is not yet clear how such covert shifts of visual attention to peripheral regions impact the processing of the targets we directly foveate as they move in our visual field. The current study utilised the coregistration of eye-position and EEG recordings while participants tracked moving targets that were embedded with a 30 Hz frequency tag in a Stea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…De Lissa et al [ 83 ] used the frequency tagging method to assess visual attention in the smooth-pursuit paradigm, where 17 participants had to follow a moving target and react when it reached the goal area (1st paradigm) or follow this target and switch their attention when the second one, flickering at 30 Hz, occurs and follow it until it reaches the goal area (2nd paradigm). Researchers found that SSVEP power decreased early and rapidly when the individuals had to divide their attention.…”
Section: Visual Attentionmentioning
confidence: 99%
“…De Lissa et al [ 83 ] used the frequency tagging method to assess visual attention in the smooth-pursuit paradigm, where 17 participants had to follow a moving target and react when it reached the goal area (1st paradigm) or follow this target and switch their attention when the second one, flickering at 30 Hz, occurs and follow it until it reaches the goal area (2nd paradigm). Researchers found that SSVEP power decreased early and rapidly when the individuals had to divide their attention.…”
Section: Visual Attentionmentioning
confidence: 99%
“…The novelty of the SSVEP effect observed is likely due to complications inherent to the sustained IB paradigm. SSVEP magnitude is attenuated when attention is divided across hemifields (Toffanin et al, 2009), directed to moving targets (De Lissa et al, 2020), and/ or is directed to targets in the periphery (Chen et al, 2017). Parsing out the isolated signal of each concurrent stimulus within the aggregate neural response also remains a challenge with the presentation of multiple simultaneous moving stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It remains undetermined whether, in the present study, participants' overt attention was automatically attracted toward the pedestrian distractors, or conversely whether they voluntarily gazed at pedestrian distractors and covertly attended to cars. This question could be addressed using the approach based on eye-tracking and Steady State Visual Evoked Potentials that we recently developed, and which allowed us to demonstrate that covert shifts of attention reduce visual processing of objects even when they are directly tracked with the eyes (de Lissa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%